2014
DOI: 10.1016/j.advwatres.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for lateral depth-averaged velocity distributions along a meander in curved compound channels

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Therefore, the conveyance capability at the middle cross-section is weaker than that at the apex. In addition, Liu et al (2014a) and Shiono and Muto (1998) have observed that the flow directions in the main channel and floodplain are the same at the apex section (CS1) and different at the middle cross-section (CS4). In summary, the flow pattern is uniform at the apex section, where the flow directions in the main channel and on the floodplain are the same.…”
Section: Flow Patterns At the Apex And The Middle Cross-sectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the conveyance capability at the middle cross-section is weaker than that at the apex. In addition, Liu et al (2014a) and Shiono and Muto (1998) have observed that the flow directions in the main channel and floodplain are the same at the apex section (CS1) and different at the middle cross-section (CS4). In summary, the flow pattern is uniform at the apex section, where the flow directions in the main channel and on the floodplain are the same.…”
Section: Flow Patterns At the Apex And The Middle Cross-sectionmentioning
confidence: 99%
“…At the apex section, the component of floodplain flow (V fp ) can be ignored because the angle between the streamwise direction and the flow direction is nearly 0° (Liu et al, 2014a). Therefore, the velocity parameter is…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations